Analisis Strategi Manajemen Perubahan: Studi Kasus pada UMKM JR Coffee Drink N Snack Lubuk Begalung Padang - Ratu Dara Saphira; Sania Audy Nabila; Syofia Raudatul Jannah; Vahra Oktaladisa; Ramdani Bayu Putra (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Abstrak. This Social Service project seeks to study and comprehend the change management practices used at the MSME "JR Coffee Drink N Snack" in Lubuk Begalung, Padang. The activities' primary focus is on corporate competition and customer behavior, both of which are thought to be crucial for enhancing organizational performance and preserving competitiveness. This project employs a case study methodology, which includes document analysis, in-depth interviews, and direct observation to provide a thorough understanding of the internal dynamics and difficulties experienced by MSMEs (Micro, Small, and Medium Enterprises) at JR Coffee Drink N Snack Padang. Strong business competition and favorable consumer behavior are important factors in increasing a company's performance, according to research findings. And this Social Service effort is likely to have an impact on improving business owners' knowledge, abilities, and awareness of similar difficulties, as well as their competitiveness in an increasingly competitive market.